Factors Affecting The Welfare of Workers in Micro and Small Enterprises (MSEs) to Achieve Sustainable Living in Palembang City - Desfitrina; Susetyo, Didik; Saleh, Rosmiyati Chodijah; Hidayat, Ariodillah (International Journal of Accounting and Economics Studies, 2025)
This study aims to identify and analyze the factors that influence the welfare of workers in Micro and Small Enterprises (MSEs) in Palembang City within the framework of sustainable livelihoods. The approach used is a quantitative approach using the survey method. The population in this study is all MSE workers in Palembang City, and the sampling technique is carried out using a proportionate stratified random sampling method by considering the representation of various business sectors and administrative areas. The number of respondents analyzed was 396 people. Data were collected through questionnaires that had been tested for validity and reliability. The analytical technique used was multiple linear regression to examine the influence of the five independent variables of human capital, social capital, natural capital, physical capital, and financial capital on the dependent variable of worker welfare. In addition, a t-test was conducted to see the partial effect, an F-test for simultaneous effect, and a coefficient of determination analysis to measure the strength of the model. The results show that the five types of capital have a positive and significant influence on workers’ welfare partially and simultaneously. Human capital, such as education, skills, and health, is the main determinant in improving individual capacity. Social capital through networks and collective trust strengthens community ties and workers’ sense of security. Natural and physical capital play a role in providing a comfortable and productive work environment, while financial capital is a crucial aspect in ensuring workers’ economic stability. The coefficient of determination shows that the model can explain part of the variation in workers’ welfare, but there are still other factors outside the model that need further investigation. Therefore, this study recommends the development of further studies by including other variables such as psychological capital, regulatory support, and qualitative approaches to enrich a holistic understanding of MSE workers’ welfare in a dynamic local context.